An analysis of power dynamics within innovation platforms for natural resource management - Cullen, Beth; Tucker, Josephine; Snyder, Katherine A.; Lema, Zelalem; Duncan, Alan J. (Informa UK Limited, 2014)
Innovation systems thinking is increasingly influencing approaches to sustainable agricultural development in developing world contexts. This represents a shift away from technology transfer towards recognition that agricultural change entails complex interactions among multiple actors and a range of technical, social and institutional factors. One option for practically applying innovation systems thinking involves the establishment of innovation platforms (IPs). Such platforms are designed to bring together a variety of different stakeholders to exchange knowledge and resources and take action to solve common problems. Yet relatively little is known about how IPs operate in practice, particularly how power dynamics influence platform processes. This paper focuses on a research-for-development project in the Ethiopian highlands which established three IPs for improved natural resource management. The ‘power cube’ is used to retrospectively analyse the spaces, forms and levels of power within these platforms and the impact on platform processes and resulting interventions. The overall aim is to highlight the importance of power issues in order to better assess the strengths and limitations of IPs as a model for inclusive innovation. Findings suggest that while IPs may achieve some short-term success in creating spaces for wider participation in decision-making processes, they may be significantly influenced by forms of power which may not always be visible or easily challenged.